Redefining Urban and Suburban America : Evidence from Census 2000 - Lang, Robert, 1959-; Katz, Bruce (Book collections on Project MUSE., 2003)
Redefining Urban and Suburban America explores demographic trends and their complexities, along with their implications for the policies and politics shaping metropolitan America. The shifts discussed here have significant influence in demand for housing and schools, childcare and healthcare, as well as private goods and services.